CEMIP Promotes Osteosarcoma Progression and Metastasis Through Activating Notch Signaling Pathway - Cheng, Jun; Zhang, Yan; Wan, Rongjun; Zhou, Jun; Wu, Xin; Fan, Qizhi; He, Jingpeng; Tan, Wei; Deng, Youwen (Frontiers in Oncology, 2022)
Cell migration inducing protein (CEMIP) has been linked to carcinogenesis in several types of cancers. However, the role and mechanism of CEMIP in osteosarcoma remain unclear. This study investigated the role of CEMIP in the progression and metastasis of osteosarcoma, CEMIP was found to be overexpressed in osteosarcoma tissues when compared to adjacent non-tumor tissues, and its expression was positively associated with a poor prognosis in osteosarcoma patients. Silencing CEMIP decreased osteosarcoma cells proliferation, migration, and invasion, but enhanced apoptosis in vitro, and suppressed tumor growth and metastasis in vivo. Mechanistically, CEMIP promoted osteosarcoma cells growth and metastasis through activating Notch signaling pathway, silencing CEMIP would reduce the protein expression and activation of Notch/Jagged1/Hes1 signaling pathway in vitro and in vivo, activation of Notch signaling pathway could partially reversed cell proliferation and migration in shCEMIP osteosarcoma cells. In conclusion, our study demonstrated that CEMIP plays a substantial role in the progression of osteosarcoma via Notch signaling pathway, providing a promising therapeutic target in osteosarcoma.